COMPANY READINESS IN APPLYING PRIVATE ENTITY FINANCIAL ACCOUNTING STANDARDS (SAK EP): A CASE STUDY OF REGIONAL OWNED ENTERPRISES (BUMD) IN YOGYAKARTA - Pranesti, Arin; Hanani, Tri (AKUNTANSI 45, 2022)
The internationalization of accounting standards is a demand for globalization so that entities become more competitive in the world market. In 2025, Indonesia through the Financial Accounting Standards Board (DSAK) will begin to adopt the Private Entity Financial Accounting Standards (SAK EP) replacing the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This study aims to determine the level of readiness of Regional Owned Enterprises (BUMD) in implementing SAK EP seen from several indicators of issuance SAK EP, recording system, presentation of financial statements, differences in financial accounting standards for entities without public accountability (SAK ETAP) and private entities (SAK EP) and availability of adequate human resources (HR). This research is a qualitative research conducted by conducting structured interviews with BUMD. The results showed that BUMD did not know the plan to change SAK ETAP to SAK EP. In addition, in terms of available resources, BUMD is deemed to need time to adjust the knowledge that needs to be possessed in order to adopt SAK EP. This research is a preliminary study to determine the initial readiness for the application of SAK EP in Indonesia. Keywords: Readiness, SAK EP, BUMD.